The value of liminal cases in developing a narrative victimology: The case of families of people serving an indeterminate sentence for public protection - Mackenzie, Kelly (Criminology & criminal justice, 2025)
This article contributes to the emerging literature on narrative victimology by examining what we will suggest to be a telling ‘liminal case’: families of people sentenced to Imprisonment for Public Protection in England and Wales. We draw on qualitative research conducted with families of people sentenced to Imprisonment for Public Protection to explore how they narrated their experiences and show that while their own predominant narratives do overlap to a considerable degree with commonly accepted victimhood frames, they fail fully to ‘fit’. We argue that such liminal cases have considerable value for the study of narrative victimology: just as ‘central’ or ‘ideal’ cases provide telling insights, the examination of the specific contours of ‘ill fitting’ case studies allows us to trace in more precise detail the boundaries – the extent, the force and the limits – of predominant narratives.